Organizational Dissent Dynamics in Universities: Simulations With a System Dynamics Model. (August 2019) - Zaini, Raafat Mahmoud; Elmes, Michael B.; Pavlov, Oleg V.; Saeed, Khalid
This article investigates how universities may evolve into high- or low-performance institutions by taking different approaches to dissent tolerance and processing. We explore different dissent management policies related to growth and productivity. We experiment with a dynamic model of dissent creation and processing in organizations presented in an earlier paper by the authors. Computer simulations with the model suggest that as universities attempt to improve their performance through growth, they may devolve into low-performance institutions with degrading management responsiveness and low organizational productivity. Only when organizations invest in their dissent processing capability will they engage their members productively for improving performance.